Impact of co‐morbidity on mortality after oesophageal cancer surgery. Issue 9 (8th June 2015) - Backemar, L.; Lagergren, P.; Johar, A.; Lagergren, J.
<x xml:space="preserve">Abstract</x> Background There is limited knowledge of how co‐morbidities influence survival after surgery for oesophageal cancer. This population‐based cohort study investigated how Charlson co‐morbidity index and specific co‐morbidities influenced all‐cause and disease‐specific mortality. Methods Data from all patients who underwent oesophageal cancer surgery in Sweden in 1987–2010, with follow‐up until 2012, came from histopathology records, operation charts and nationwide registers. Associations between co‐morbidities (Charlson co‐morbidity index) and mortality were analysed using Cox proportional hazard regression with adjustment for potential confounding, and presented as hazard ratio (HR) with 95 per cent c.i. Results Among 1822 patients there were 1474 deaths (80·9 per cent), of which 1139 (77·3 per cent) occurred between 91 days and 5 years after surgery. Overall all‐cause mortality was increased in patients with a Charlson score of 2 or more (HR 1·24, 95 per cent c.i. 1·08 to 1·42), and those with a history of myocardial infarction (HR 1·23, 1·01 to 1·49) or congestive heart failure (HR 1·31, 1·04 to 1·67). Patients with squamous cell carcinoma had increased overall all‐cause mortality if they had been diagnosed with cerebrovascular disease (HR 1·35, 1·00 to 1·83) or other cancers (HR 1·36, 1·09 to 1·71), whereas those with adenocarcinoma did not. A Charlson score of 1 or exposure to the co‐morbidity groups peripheral vascular disease, chronic pulmonary disease, connective tissue disease, peptic ulcer disease, diabetes and liver disease did not increase mortality. The disease‐specific results were generally similar to the all‐cause mortality data. Conclusion Co‐morbidity with a Charlson score of 2 or more, previous myocardial infarction and congestive heart failure were associated with increased mortality after oesophageal cancer surgery undertaken with curative intent.